Instruments for Assessment of Mathematics Learning Outcomes of Fourth-Grade Elementary School Students - Ni Putu Mia Ari Yantini; I Made Suarjana; Made Sumantri (Universitas Pendidikan Ganesha, 2021)
Teachers still do not pay attention to the minimum standards or basic competencies that must be achieved by students, so that in making assessment questions it is not according to students' abilities and the achievement of basic competencies from the subject matter being studied. This study aims to create an instrument for assessing mathematics learning outcomes for fourth grade elementary school students. This type of research is development research. The model used in this study is using the ADDIE model. The subjects used were 2 mathematicians/experts and 30 students as respondents. Data collection techniques are observation, interviews, document recording, tests. The results of the study were analyzed with validity and reliability showing the number of valid items as many as 18 items that were declared valid and 2 items that were not valid. After that, the reliability test was carried out using the Kuder Richardson 20 (KR-20) formula with the help of the Microsoft Office Excel application. The results of the calculation of instrument reliability obtained r11 = 0.82 has a